Health literacy assessment and healthcare access difficulties of Vietnamese migrants in Japan: A cross-sectional study - Takashi Tsubakita; Nobuo Kawazoe; Nobuyuki Matsuo (PLoS ONE, 2026)
While the number of Vietnamese migrant workers in Japan has been increasing, their healthy literacy as a key concern for ensuring equitable access to healthcare is unknown. This study assessed health literacy among Vietnamese migrants in Japan and examined their access to healthcare and the difficulties they encounter. Convenience sampling was employed, with Vietnamese support organizations across Japan invited to disseminate a web-based survey via social media platforms. Using both self-reported and test-based health literacy tools, we measured health literacy levels in a sample of 137 Vietnamese migrants. We identified disparities by gender and topic area, where women were likely to score higher than men, particularly in mental health and knowledge of sexually transmitted infections. Our findings underscore the importance of culturally tailored health education and community-based interventions to support the health of this population. The study highlights the need for cultural and linguistically adapted educational materials to improve equitable access to healthcare. Our work contributes to the ongoing dialogue on migrant health and the development of inclusive public health strategies.